2013
DOI: 10.1111/coep.12010
|View full text |Cite
|
Sign up to set email alerts
|

Economic Freedom of the World: An Accounting of the Literature

Abstract: and has been updated annually since. During this period, the EFW index has been cited in hundreds of academic articles. Here, we provide an accounting and description of this literature. Of 402 articles citing the EFW index, 198 used the index as an independent variable in an empirical study. Over two-thirds of these studies found economic freedom to correspond to a "good" outcome such as faster growth, better living standards, more happiness, etc. Less than 4% of the sample found economic freedom to be associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
209
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 381 publications
(215 citation statements)
references
References 19 publications
1
209
0
5
Order By: Relevance
“…This is also the case with Hall and Lawson (2014), who made an overview of empirical studies using the Economic Freedom Index of Fraser Institute. They found that over two-thirds of 198 studies found a positive impact of economic freedom on well-being, while only 4% found a negative impact.…”
Section: Economic Freedom and Income Inequalitymentioning
confidence: 93%
“…This is also the case with Hall and Lawson (2014), who made an overview of empirical studies using the Economic Freedom Index of Fraser Institute. They found that over two-thirds of 198 studies found a positive impact of economic freedom on well-being, while only 4% found a negative impact.…”
Section: Economic Freedom and Income Inequalitymentioning
confidence: 93%
“…The vast majority of cross-country empirical studies have linked economic freedom to positive outcomes (Hall and Lawson, 2014). The studies by Bennett, Boylan and Cebula in Chapter 9 and Cebula in Chapter 11 further affirm this.…”
Section: The Benefits Of Economic Freedom: Is Greater Equality One Ofmentioning
confidence: 90%
“…Faria and Montesinos (2009) found a "robust association between economic freedom and prosperity". In their literature review on this subject using the Economic Freedom of the World index, Hall and Lawson (2014) indicate that over two-thirds of the existing studies found that economic freedom is related to positive outcomes such as faster growth, better living standards, and more happiness. When examining the economic freedom and economic growth nexus in a panel of 28…”
Section: Literature Reviewmentioning
confidence: 99%